‘What do I need to Know?’: A Narrative Inquiry of Experiences and Expectations for Addressing the Needs of English language learners (ELLs) (Universitas Negeri Semarang, 2023)
Teaching English language learners is the initial phase of language education programs for English language teachers when they are introduced to a child's world, developmental traits, needs, and interests as well as teaching and learning approaches for their learners. This study, which employs the qualitative approach of narrative inquiry, shares personal accounts of the researcher's experiences and expectations in an attempt to expand knowledge about the most effective ways to teach English to young students. The results imply that English teachers should motivate ELLs to acquire the language, offer interactive language worksheets as in-class activities, and see mistakes as learning opportunities. The findings also revealed how important it is to include technology into learning environments and give ELLs opportunities to practice their language skills. The findings of the study have implication for both present and future research, but primarily for English practice and education.